Arms trafficking and Colombia - Cragin, Kim (RAND, National Defense Research Institute, 2003)
Colombia has experienced significant political instability and violence over the past century due to a number of factors, including the proliferation of small-arms trafficking. The authors identify the sources and routes used by arms traffickers to acquire, buy, sell, receive, transfer, and ship weapons. They also examine the various groups and individuals who purchase and use these munitions. The authors examine Colombia?s political conflict through the lens of small-arms trafficking and conclude with policy implications for the United States.